Physical preparation of female judo competitors at selected stages of long-standing sports training - Jagiello, W.; Wolska, B.; Smulski, W. (Archives of Budo, 2009)
Background: It is currently assumed in sports theory and practice that general and special physical preparation is an indispensable condition for the development of motor skills as one of the most important factors determining the effectiveness of athletes' training and competition activity. Therefore, the aim of the study is an analysis of correlative connections between indices of judo competitors' general and special physical preparation at various stages of long-standing training. Material/Methods: The paper presents the results of studies on general and special physical preparation of three groups of female judo competitors: eleven Polish national team representatives in the senior category (the stage of maximal realisation of individual capabilities), fifteen Polish national team and Pomerania Province team representatives in the category of juniors (the stage of directed training), and fourteen Pomerania Province team representatives in the category of sub-juniors and younger juniors (the stage of general training). General physical preparation was assessed on the basis of the International Physical Fitness Test (IPFT), and the special one on the basis of Special Judo Fitness Test (SJFT). Results: Competitors from all groups are characterised by high IPFT indices. The studied group of seniors exceed 16-18-year-old competitors in a statistically significant way, who in turn exceed the 13-15-year-old ones as far as results obtained in the SJFT test are concerned. Highly-qualified competitors are characterised by more expressed and direct interdependence between the IPFT and SJFT test indices in comparison with the studied groups of 16-18-year-old and 13-15-year-old competitors. Conclusions: With increase in judo competitors' sports level, the number and the level of these mutual relations also increases.